The health burden of disease attributable to low calcium intake: a comprehensive analysis of trends and socioeconomic impacts from 1990 to 2021 - Wang, Yanping; Tao, Meihui; Wang, Li; Zhou, Siyu; Yang, Weifeng; Zhao, Xi; Feng, Qinyu; Tang, Mengfan; Yan, Wei; Fu, Yu (Frontiers in Nutrition, 2025)
BackgroundCalcium, a vital nutrient for the human body, is indispensable for keeping our bones strong and managing cell function. A diet low in calcium (DLC) is a key player in the formation of numerous health issues. This research delved into the most recent datasets acquired via the 2021 Global Burden of Disease (GBD) report to uncover the worldwide impact of DLC.MethodsUtilizing the GBD 2021 database, this research examined the association of DLC with disease burden, covering colorectal and prostate cancers. To quantify disease burden and track its temporal variations, key indicators were employed. These included deaths, disability-adjusted life years (DALYs), age-standardized mortality rate (ASMR), age-standardized DALY rate (ASDR), and the estimated annual percentage change (EAPC). The analysis broke down results by sex, age brackets, Socio-demographic Index (SDI) categories, and geographic regions. To examine potential links between disease burden and socioeconomic factors, Pearson's correlation method was applied. Furthermore, Bayesian age-period-cohort (BAPC) modeling was applied to forecast trends spanning 2022–2050.ResultsFrom 1990 to 2021, global colon and rectum cancer (CRC)-related deaths tied to DLC rose from 57,363 to 89,089, while the ASMR decreased from 1.54 to 1.06 per 100,000 [EAPC = −1.33 (95% CI: −1.37 to −1.29)]. DALYs increased from 1,512,762 to 2,128,939, and the ASDR declined from 37.04 to 24.7 per 100,000 [EAPC = −1.45 (95% CI: −1.50 to −1.40)]. The burden of CRC tended to escalate with age, and it disproportionately affected women more than men. However, the impact on women diminished more rapidly over time. Prostate cancer and DLC showed a negative directional trend but lacked statistical significance. CRC burden showed a negative correlation with SDI, while prostate cancer burden had a positive association.ConclusionDLC significantly increases the incidence of CRC, while its impact on prostate cancer incidence is relatively minor and shows a negative correlation. Both phenomena are closely associated with socioeconomic development. The research yields essential data to develop focused dietary interventions and cancer-prevention policies.